One-pot sonochemical synthesis of hierarchical MnWO4 microflowers as effective electrodes in neutral electrolyte for high performance asymmetric supercapacitors. (23rd April 2019) - Raj, Balasubramaniam Gnana Sundara; Acharya, Jiwan; Seo, Min-Kang; Khil, Myung-Seob; Kim, Hak-Yong; Kim, Byoung-Suhk
Abstract: In this article, manganese tungstate (MnWO4 ) microflowers as electrode materials for high performance supercapacitor applications are prepared by a one-pot sonochemical synthesis. The crystalline structure and morphology of MnWO4 microflowers are characterized through X-ray diffraction, field emission scanning electron microscopy. The electrochemical properties of the MnWO4 microflowers are investigated using cyclic voltammograms, galvanostatic charge/discharge and electrochemical impedance spectroscopy. The MnWO4 microflowers as electrode materials possess a maximum specific capacitance of 324 F g −1 at 1 mA cm −2 in the potential window from 0 to +1 V and an excellent cycling stability of 93% after 8000 cycles at a current density of 3 mA cm −2 . An asymmetric supercapacitor device is fabricated using the MnWO4 and iron oxide (Fe3 O4 )/multi-wall carbon nanotube as the positive and negative electrode materials, it can be cycled reversibly at a potential window at 1.8 V. The fabricated ASC device can deliver a high energy density of 34 Wh kg −1 at a power density of 500 W kg −1 with cycling stability of 84% capacitance retained after 3000 cycles. The above results demonstrate that MnWO4 microflowers can be used as promising high capacity electrode materials in neutral electrolyte for high performance supercapacitors. Graphical abstract: Image 1 Highlights: Hierarchical MnWO4 assembled microflowers via one-pot sonochemical synthesis. MnWO4 nanoflakes deliver a maximum specific capacitance of 324 F g −1 at 1 mA cm −2 . Excellent cycling stability of 93% its initial capacitance after 8000 cycles. Asymmetric device delivers high energy density of 34 Wh Kg −1 at 500 W kg −1 .